Sir Charles Bell : His Life, Art, Neurological Concepts, and Controversial Legacy. - Aminoff, Michael J. MD, DSc, FRCP (Oxford University Press, 2016)
Sir Charles Bell (1774-1842), the Scottish anatomist-surgeon, was a true polymath. His original ideas on the nervous system have been likened to those of William Harvey on the circulation of blood, and his privately published pamphlet detailing his ideas about the brain has been called the Magna Carta of neurology. He described the separate functions of different parts of the nervous system, new nerves and muscles, and several previously unrecognized neurological disorders, and he characterized the features of the facial palsy and its associated features now named after him. His sketches and p.